Hubungan Kecanduan Bermain Game Online Dengan Depresi Pada Siswa SMP - Ahmad Fikri Zaelani; Octa Reni Setiawati; Sri Maria Puji Lestari (Program Studi Psikologi Universitas Malahayati, 2019)
Game Online Addiction and Depression Among Middle School Students Popular products that are nowadays massively used among teenagers are video games and online games. It can lead to an addiction and increase the risk of depression, poor social relationships with family and friends. It often causes an isolation from society and delivers a bigger chance to psychiatric disorders. This study aims to findrelationship between online games addiction and depression in Junior High School students in Bandar Lampung. This study was a cross sectional study. The sample of this study was 546 junior hign school students in Bandar Lampung. The datawas obtained by Beck Depression Inventory and online gaming addiction scale. Data analyzed by spearman correlation. Spearman analysis test result shows a significant relationship between game online addiction and depression (r = 0.999, p <0.001). The results shows that addiction to play online games can cause depression in adolescence.Salah satu produk teknologi internet yang digemari dikalangan remaja saat ini adalah game online. Bermain game online terlalu sering dapat menambah resiko depresi. Penelitian ini bertujuan untuk mengetahui hubungan antara kecanduan bermain game online dengan depresi pada siswa SMP. Penelitian ini merupakan penelitian analitik dengan pendekatan cross sectional. Sampel penelitian adalah 546 siswa SMP se- Kota Bandar Lampung. Pengambilan data menggunakan back depression inventory dan kuesioner kecanduan bermain game online. Analisis data hasil penelitian dilakukan dengan uji korelasi Spearman. Hasil uji analisis Spearman didapatkan hubungan yang signifikan antara kecanduan bermain game online dengan depresi (r = 0,999, p < 0,001). Hasil penelitian menunjukkan bahwa kecanduan bermain game online dapat menimbulkan depresi pada remaja.